Media Pamflet dan Alat Peraga Phantom dalam Rangka Meningkatkan Pengetahuan Karies Gigi pada Anak - Mariana Koch, Novarita; Raule, Jean Henry; Bugis, Sartika (Bhakti Persada Jurnal Aplikasi IPTEKS, 2024)
Knowledge is acquired in education from an early age including elementary school. Elementary school children are the main target for improving dental health. This improvement requires appropriate promotional media to support dental health promotion so that a theoretical understanding of the related material can be achieved. This research aims to evaluate the effectiveness of pamphlet media and demonstration of dental phantom props on children's knowledge level of dental caries. The study was conducted with a Quasi-Experimental research type with a "Two group pretest posttest design". It was carried out in June 2022 at SD GMIM 28 Manado City. The sample of the population, namely 40 students, was divided into 2 groups, namely 20 samples using pamphlet media and 20 samples using the dental phantom demonstration method. Knowledge measurement using a questionnaire. Data analysis was performed through paired t-test statistical tests. The study's results used a paired t-test with df = 19 resulting in p = 0.000 for etiher pamphlet or dental phantom media. The t-value of the pamphlet media was -71.53, greater than the t-value of the demonstration using a phantom with a value of -4.397. This study concludes that pamphlet media is more effective than phantom media in increasing knowledge of dental caries in children.